Estimation of the wild‐type minimum inhibitory concentration value distribution. (15th August 2013) - Jaspers, Stijn; Aerts, Marc; Verbeke, Geert; Beloeil, Pierre‐Alexandre
<x xml:space="preserve">Abstract</x> Antimicrobial resistance has become one of the main public health burdens of the last decades, and monitoring the development and spread of non‐wild‐type isolates has therefore gained increased interest. Monitoring is performed based on the minimum inhibitory concentration (MIC) values, which are collected through the application of dilution experiments. In order to account for the unobserved population heterogeneity of wild‐type and non‐wild‐type isolates, mixture models are extremely useful. Instead of estimating the entire mixture globally, it was our major aim to provide an estimate for the wild‐type first component only. The characteristics of this first component are not expected to change over time, once the wild‐type population has been confidently identified for a given antimicrobial. With this purpose, we developed a new method based on the multinomial distribution, and we carry out a simulation study to study the properties of the new estimator. Because the new approach fits within the likelihood framework, we can compare distinct distributional assumptions in order to determine the most suitable distribution for the wild‐type population. We determine the optimal parameters based on the AIC criterion, and attention is also paid to the model‐averaged approach using the Akaike weights. The latter is thought to be very suitable to derive specific characteristics of the wild‐type distribution and to determine limits for the wild‐type MIC range. In this way, the new method provides an elegant means to compare distinct distributional assumptions and to quantify the wild‐type MIC distribution of specific antibiotic–bacterium combinations. Copyright © 2013 John Wiley & Sons, Ltd.